Selenoamides modulate dipole–dipole interactions in hydrogen bonded supramolecular polymers of 1, 3, 5-substituted benzenes. Issue 99 (26th November 2019) - Berrocal, José Augusto; Mabesoone, Mathijs F. J.; García Iglesias, Miguel; Huizinga, Alex; Meijer, E. W.; Palmans, Anja R. A.
Abstract : Selenoamide moieties introduced into C 3 -symmetrical molecules enhance supramolecular interactions and confer a remarkable thermal stability to the supramolecular polymers. Abstract : We report the synthesis and self-assembly behavior of a chiral C 3 -symmetrical benzene-tricarboselenoamide. The introduction of the selenoamide moiety enhances the dipolar character of the supramolecular interaction and confers a remarkable thermal stability to the supramolecular polymers obtained.